Semiconductor Supply Chain Efficiency: A PLM-Powered Optimization Strategy - Khastgir, Antara; Krishnan, Manish (International Journal of Supply Chain Management, 2024)
Semiconductors are one of the most indispensable components that shore up modern society, as is evident from their extensive presence in majority of the products that we use every day and are dependent on. Being a key component of electronic devices, semiconductors enable improvements and progression in information and communication technology (ICT). It affects all round advancements affecting almost all the aspects of modern life - from computing, to communications, healthcare to transportation, military systems to clean energy, and several other applications. Semiconductors form an important part of our daily lives because of the role they play in the manufacture of electronic devices. This study scrutinizes existing literature to provide insight into the necessity of using PLM is the optimization of semiconductor supply chain and heightening of efficiency